Computational Biology Service Unit: Cornell University Core Facility for Computational Biology - Sun, Q. (Association of Biomolecular Resource Facilities, 2010)
CF-3 The Computational Biology Service Unit (CBSU) of the Cornell University Life Sciences Core Laboratories Center (CLC) provides bioinformatics and computational biology resources and services to the university community and to outside investigators. The CBSU is Microsoft Biology Initiative partner and charter member of Microsoft High Performance Computing Institute program. Facility resources include a set of servers and compute clusters with over 1200 cores. The goal of the facility is to meet the increasing need of Cornell investigators for broad support in computational biology and bioinformatics.